STATE REGULATION OF ECONOMY AND ENSURING NATIONAL INTERESTS IN THE USA: SOME INSTITUTIONAL ASPECTS - T. Kovaleva (Вестник университета)
In the article analyzed some institutional aspects of state regulation of the economy on the USA, the structure, status and powers of the Bureau of Industry and Security in the United States Department of Commerce, determined кеу parameters of its influence on strategic industries.